Effects of NSC in different organs and at different growth stages on the yield of oil peony Fengdan with different ages - Wang, Chengzhong; Ma, Xiaoyi; Li, Qingkui; Hu, Yonghong; Yang, Ji; Song, Zhiping (Frontiers in Plant Science, 2023)
Non-structural carbohydrates (NSC) as resource reserves of plants play important roles in energy supply for normal growth and reproduction under environmental stress. The yield of perennial crops is mainly determined by the carbohydrate production and allocation in the current growth season, as well as the re-allocation of NSC reserves. However, the contribution of NSC to crop yield has not been fully determined. Fengdan (Paeonia ostii) is a variety of oil Peony that is newly developed in China. The effects of tree age and NSC on yield were examined by investigated the variations of biomass, soluble sugars, starch, and NSC in the organ and whole tree levels in the dormant and ripening stages of Fengdan populations with 4-, 6-, and 8-year-old in 2020 and 5-, 7-, and 9- year old in 2021. Results showed that the biomass, yield (seed biomass), soluble sugars, starch, and NSC reserve of Fengdan at the whole tree level increased with the increase in age. Although consistent correlations were observed between soluble sugars, starch and NSC storage, and yield among the plants with different ages, Fengdan showed allometric growth relationships between the accumulation of soluble sugars, starch, and NSC and yield and biomass (standardized major axis analyses slope b ≠ 1). Tree age significantly affected biomass and its allocation and NSC levels, especially the yield of Fengdan plants. The results of the investigation of the variations in the relationships between the yield and seasonal fluctuations of NSC and biomass indicate that roots is the key storage structure, whereas stems both serve as sink and/or source functions for the adult (7–9a) plants. NSC level, particularly the concentration of soluble sugars, in stems mainly influences Fengdan yield. These findings together provide new insights into the mechanisms underlying the yield formation of Fengdan and have implications for manipulating sink-source relationship to achieve high yield.